PROFIL KEBERHASILAN PEMASANGAN INTRAVENA KATETER DI MAYAPADA HOSPITAL SURABAYA - Ari Sunari; Imelda Imelda; Yustina Yustina (CV. ADIBA AISHA AMIRA, 2025)
Intravenous catheter (IVC) insertion is one of the most frequently performed nursing procedures in hospitals and plays a vital role in intravenous therapy, both for the administration of fluids, drugs, and transfusions. The success of this procedure directly affects patient safety, service efficiency, and the quality of nursing care. However, various studies have shown that the success rate of IVC insertion on the first attempt is still low globally, and contextual data in Indonesia, especially in private hospitals, is still very limited. This article aims to describe the profile of IVC insertion success at Mayapada Hospital Surabaya and identify the factors that contribute to its achievement. This study uses a retrospective descriptive approach with analysis of IV insertion recap data during the period April 2024 - July 2024. The results show that the success rate of IVC insertion on the first attempt at this hospital is above the national average, with significant contributions from practice-based training, clinical supervision, and the use of standard procedural guidelines. These findings provide theoretical contributions in enriching the literature related to nurses' technical competence and provide practical implications in the form of recommendations for improving the quality of nursing services through strengthening training programs and performance evaluation. This study is also expected to be the basis for the development of institutional policies and comparative studies in other health facilities in Indonesia.